Multi-Doping Of Mg-Co Substituted Carbonated Hydroxyapatite For Biomedical Applications - Yahaya, Syahidah Suhaili (Universiti Sains Malaysia, 2017)
Carbonated hydroxyapatite (CHA) is a promising biomaterials that is suitable to be used as bone substitution. However, CHA has limitation, as it has low thermal stability. Thus, this study was conducted to investigate the effect of multi-doped CHA through chemical, mechanical, physical and biological analysis. Multi-doped CHA was successfully synthesis via nanoemulsion method, through direct pouring technique, followed by characterizations of the produced powders. It was found that Mg-Co CHA 1 and Mg-Co CHA 2 had the optimum compositions. The powders produced were B-type CHA. These powders were then fabricated by dry pressing method and sintered at 900°C. Dry carbon dioxide (CO2) gas was supplied to the sample after cooled down to 200°C to compensate carbonate decomposition during sintering. Used of dry CO2 had successfully compensate the carbonate decomposition during sintering. The sintered samples were maintained as B-type CHA. In vitro bioactivity test also was done for sintered multi-doped CHA for seven days. SEM observation for dense multi-doped CHA after seven days showed that apatite layer were successfully formed for all compositions. Thus, the optimum composition that produced high amount of apatite layer, good chemical, mechanical and physical properties is Mg-Co CHA 2, where magnesium in maximum amount and cobalt in minimum amount.